Study on Cold Chain Logistics Operation and Risk Control of Fresh e-Commerce Products - Shenxiang Wang (Advances in Multimedia)
With the rapid development of the Internet, my country’s e-commerce market has been very active in recent years, and the number of e-commerce platforms and the volume of product transactions have achieved rapid development. However, through the investigation of the main circulation products of e-commerce brands, it can be found that the output value of my country’s e-commerce industry as a whole in the fresh food field is very low. Many fresh products are prone to various risks during the circulation process, resulting in large losses on the platform and online agricultural products e-commerce. There is a shortage of fresh cold chain equipment and cold chain technicians, which directly affects the stable and healthy development of fresh cold chain logistics in China. This paper analyzes the existing operation mode of e-commerce, analyzes the main bottleneck of the operation of the fresh cold chain, and puts forward corresponding suggestions to enhance the awareness of risk control, so as to better promote the benign operation of agricultural products cold logistics and provide some reference for the optimization of e-commerce fresh cold chain logistics.